1985
DOI: 10.1017/s0195941700061737
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Pneumonia Caused by Gentamicin, Methicillin-Resistant and Gentamicin, Methicillin-SensitiveStaphylococcus aureus: Epidemiologic and Clinical Studies

Abstract: We investigated an outbreak of nosocomial pneumonia due to gentamicin, methicillin-resistant Staphylococcus aureus (GMRSA). We compared the predisposing factors for pneunomia due to GMRSA to those for pneumonia due to gentamicin, methicillin-sensitive Staphylococcus aureus (GMSSA). Seventeen of 29 patients with staphylococcal pneumonia were infected with GMRSA. Risk factors and associated diseases which selected for infection with GMRSA as opposed to GMSSA included prior antibiotic therapy for a prolonged peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
2
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
0
20
2
1
Order By: Relevance
“…However, the results of the current contribution contradict those of two clinical studies on the same issue that did not fulfil the present inclusion criteria [25,26]. The fact that these two studies did not establish any association between methicillin resistance and excess mortality may not be surprising.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…However, the results of the current contribution contradict those of two clinical studies on the same issue that did not fulfil the present inclusion criteria [25,26]. The fact that these two studies did not establish any association between methicillin resistance and excess mortality may not be surprising.…”
Section: Discussioncontrasting
confidence: 87%
“…It is noteworthy that several investigators have reported that patients with MSSA infections experience worse clinical outcomes when treated with vancomycin rather than a b-lactam [27][28][29]. In the other study [26], several methodological issues (such as the enrolment of patients not receiving mechanical ventilation, as well as the absence of an accurate microbiological confirmation of the pneumonia diagnosis based on quantitative cultures) might have substantially influenced its findings. Likewise, three [18,20,24] of the eight articles included in the present review also demonstrate no relationship between methicillin resistance and mortality in patients with S. aureus VAP.…”
Section: Discussionmentioning
confidence: 97%
“…The quinolone antibiotics have been proposed as a possible alternative to parenteral vancomycin therapy on the basis of in vitro (1,3,21) and in vivo animal model (6) data. The present study was undertaken to compare the activities of several of the fluoroquinolone antibiotics and vancomycin against strains of gentamicin-and methicillin-resistant S. aureus, which has become a major pathogen at our institution (13).…”
mentioning
confidence: 99%
“…Meantime, some of the European countries have shown a wide range of MRSA bacteremia proportions (0% in Iceland to 52.4% in Malta) and a few countries such as France, the UK, and Slovenia have demonstrated a decline in MRSA bacteremia rates over recent years due to the implementation of multifaceted prevention programs [16]. Therefore, compared to other countries, THA, Sri Lanka shows a comparatively low prevalence of MRSA bacteremia.…”
Section: Discussionmentioning
confidence: 99%